Formulation and evaluation of enteric coated tablet of Ilaprazole - Rathore, Surya Bhan Singh; Sharma, Anshu; Garg, Ayush; Sisodiya, Dharmendra Singh (International Current Pharmaceutical Journal, 2013)
The present study was an attempt to formulate and evaluate enteric coated tablets for Ilaprazole to reduce the gastrointestinal tract side effects. Four formulations of core tablets were prepared and one who shows rapid disintegration (near around three minutes) was selected for enteric coating. Ilaprazole which have an irritant effect on the stomach can be coated with a substance that will only dissolve in the small intestine. Enteric coat was optimized using two different polymers such as HPMCP 50 and Eudragit L 100 in different concentrations. The prepared tablets were evaluated in terms of their pre-compression parameters, physical characteristics and in-vitro release study. 2.5% seal coating on core tablets was optimized and 9% enteric coating on seal coated tablets was performed using HPMC P 50 (60%), triethyl citrate (10%) and IPA:DCM (60:40) which gives the highest dissolution release profile and f2 value. DOI: http://dx.doi.org/10.3329/icpj.v2i7.15156 International Current Pharmaceutical Journal, June 2013, 2(7): 126-130